MODEL PEMBELAJARAN MEMBACA PEMAHAMAN BERBASIS STRATEGI BELAJAR METAKOGNISI - Riyadi, Iswan; -, Hersulastuti; Nugrahaningsih, Theresia Kriswianti (Universitas Muhammadiyah Semarang, 2015)
This research is based on researchers’ previous finding over teachers’ complaint on the implementation of curriculum 2013. The low achievement of students’ reading comprehension has long been related to the low motivation of students in reading. This situation has been considered as sighnificant obstacle when the phases of scientific based learning are implemented in learning process. In general, this research and development is aimed at inventing a learning model of reading comprehension that is based on metacognitive learning strategy in the lesson of Bahasa Indonesia at SMP Klaten. The purpose of the first year: to describe learning strategy that has been employed by teachers. The second year: to develop learning model of metacognitive learning strategy in the lesson of Bahasa Indonesia. Third year: to conduct extended implementation by testing validity, practicallity and effectiveness of the model . In the first year, this research was carried out in four SMP, while in the second year was conducted in two schools. The data collection techniques used in this study were, observation, interview, document analysis, FGD, and questionnaire. To analyze the data, interactive model, evaluative analysis, and comparative analysis were employed. The result of the firs year shows that: (1) reading comprehension is carried out in different time allotment in Bahasa Indonesia learning; (2) teachers use reading aloud as the strategy to teach reading comprehension; (3) teachers are less intensive in guiding students; (4) teachers train students to answer 5W+1H. Meanwhile, the result of the second year shows that: (1) students master the metacognitive learning strategy consists of: underlining, note taking, summarizing, and concept maping; (2) students’ reading comprehension skills are improving; (3) learning beomes more meaningful; (4) students’learning autonomy is increasing. This research will be continued in 2016 to test the validity, practicallity, effectiveness, and dissemination of the model.Keywords: metacognitive, learning strategy, reading comprehension